The establishment of the Syrian Orthodox Patriarchate press - Taşğın, Ahmet; Langer, Robert (Historical aspects of printing and publishing in languages of the Middle East, 2014)
"The Establishment of the Syrian Orthodox Patriarchate Press" published on 01 Jan 2014 by Brill.